Mitigating Social Fatigue - Luhur, Calista; Haqi Putri, Id'hayani Shavana; Pangaribuan, Christian Haposan (Business and Entrepreneurial Review, 2023)
With the increasing technology adoption across all ages throughout the population, number of social media users increases and shows no stopping. Positive benefits of social media are widely reported with increased in well-being and life satisfaction. On the other hand, many users have decided to take a social media detox or even discontinue to use social media as they feel fatigued by it. This research aims to study what factors that may lead users to social media fatigue as well as provide possible solutions to help users derived more positive benefits compared to negative ones. This study is conducted through an online survey with 115 samples with most coming from Gen- Z and millennials, the samples are then analyzed with the SMART PLS 4 software. The study findings are that the three variables: boredom proneness, information overload and depression have correlation to social media fatigue with information overload being the most significant as seen from p value (0,0000). The study concludes that these three variables have positive significance to social media fatigue.